A generalized multichannel least squares lattice algorithm based on sequential processing stages - Fuyun Ling; Proakis, J. (IEEE transactions on acoustics, speech, and signal processing, 1984)
A generalized multichannel least squares (LS) lattice algorithm which is appropriate for multichannel adaptive filtering and estimation is presented in this paper. It is shown that a muitichannel LS estimation algorithm with a different number of parameters to be estimated in each channel can be implemented by cascading lattice stages of nondescending dimension to form a generalized lattice structure. A new realization of a multichannel lattice stage is also presented. This realization employs only scalar operations and has a computational complexity of 0(p 2 ) for each p-channel lattice stage.